2018
DOI: 10.1016/j.jval.2018.09.2610
|View full text |Cite
|
Sign up to set email alerts
|

Psy33 - Feasibility of Evaluating the Burden of B-Thalassemia With German Claims Data

Abstract: were used to estimate the age-adjusted national prevalence of diagnosed HCU and PKU patients. RESULTS: Among 97.3 million patients in the MSN, 6,613 (0.068 per 1,000) had a diagnosis of HCU between 1/1/2010 and 12/31/2016, compared to 5,120 (0.053 per 1,000) with a PKU diagnosis. Of the HCU cases, 0.51% were ages 0e11 years and 80% were 45 years or older at the time of the first recorded diagnosis during the study period. For PKU cases, 53% were ages 0e11 years and 13% were 45 years or older. The estimated age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In 14 (61%) of these studies, only beta‐thalassemia was reported 5,21,28,30–32,34,36,38,41–45 . No papers reported solely alpha‐thalassemia.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 14 (61%) of these studies, only beta‐thalassemia was reported 5,21,28,30–32,34,36,38,41–45 . No papers reported solely alpha‐thalassemia.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 studies reported population‐based estimates of beta‐thalassemia; data were from North America (including US 20,28 and the US and Canada combined 27 ), Europe (Denmark, 29 England, 24,30 France, 21,31 Germany, 32 Greece, 33 Italy, 34 the Netherlands, 35 Spain, 36,37 and the UK 38 ), Asia (Malaysia 39 and Taiwan 5 ), the Middle East (Oman, 22 Iran, 41,42 Iraq 43,44 ), and 1 country in Africa (Algeria 45 ), ranging from 0.2/100 000 people in Spain 37 in the period 2014–2017 to 49.6/100 000 people in Najaf (Iraq) in the period 2003–2018 44 (Table 1 and Figure 3A). For a limited number of countries (US, England, France, Iran, Iraq), more than one study was found in which beta‐thalassemia was reported and prevalence estimates varied moderately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations